Implications of the COVID-19 Crisis on the Administration of Philippine Diplomacy - Bautista, Miguel R. (Philippine Journal of Public Administration; Vol 64 No 2 (2020), 2022)
The COVID-19 pandemic is widely recognized as one of the most important challenges that humanity currently faces. It has had a greater disruptive effect on the world than recent wars and has caused greater social disruption than most upheavals in the modern age with the continuing effects of the pandemic threatening the established order of global governance and international relations. These challenges make clear that Philippine foreign policy is at a crossroads. This article examines the implications of the COVID-19 pandemic on the administration of Philippine diplomacy. It discusses the economic and political impact of the COVID-19 pandemic. The discussion zooms in to how the pandemic affects the foreign service sector. The article concludes with some implications for the administration of Philippine diplomacy.
Keywords: Philippines, diplomacy, public administration, COVID-19 implications